LITERASI INFORMASI TENAGA PENDIDIK DAN KEPENDIDIKAN PENDIDIKAN NONFORMAL (PNF) DI PROVINSI DKI JAKARTA - Adelina Bachtar, Mulni; Sismita, Arifah; Purnomowat, Sri (BACA: Jurnal Dokumentasi dan Informasi, 2009)
The aim of this research is to identify the awareness, competency level, and constraints of information literacy among non-formal education tutors in DKI Jakarta Capital Special Territory. There are forty seven (or 94%) respondents from the tutor population in DKI Jakarta. Data was collected by using questionnaires and in-depth interviews. The research findings show that most respondents stated that they understand information literacy terminology. he respondents can evaluate and manage information they found. Although this competency has not meet information literacy standards yet, they able to find information to meet their immediate needs. According to the respondents, the biggest constraint on information literacy lays on their own effort and willingness, their lack of motivation and skill to find information. The external constraints include lack of information access infrastructure (and facilities), and due to the high cost of retrieving information. In order to support tutor’s tasks and activities, the respondents stated that they need courses and training, especially regarding information searching, foreign languages, introduction to computer and internet access, research methodology, and scientific writing. This research recomend to improve tutor’s information literacy competece especially information retrieval, information repackaging, and writing skills.